Literature Review: The Impact of the Covid-19 Pandemic on Reproductive Health in Women of Childbearing Age - Rotinsulu, Bela Fransiska (Journal for Research in Public Health, 2021)
ABSTRACT During the COVID-19 pandemic, many women of childbearing age experienced impacts on their reproductive health, the impacts were; menstrual cycle disorders (of 1031 participants, 53% experienced PMS), stress (of 220, (44.56% experienced stress)), physical and sexual violence (of 682 participants, 24.6% experienced psychological violence and 8.3% physical violence ), high risk during childbirth (8,207 mothers gave birth with Covid (a third, 31.5% were admitted to hospital for treatment)), unplanned pregnancy (from 30 participants 23 mothers (76.7%) became pregnant due to the advice to stay at home during Covid-19), potential to experience infertility (only 1.8% still require further research). For this reason, knowledge and protection for women is important in facing this pandemic. Literature sourced from database Google scholar, pubmed, cochrane published from 2020 to 2021, and manually selected articles relevant to the research statement. The keywords used are (Kespro, WUS, impact of the Covid-19 pandemic). The journals found were then screened based on appropriate topics and the year the journal was published, resulting in 9 journals being reviewed. Based on the research results of 9 journals that were reviewed, it was concluded that during the COVID-19 pandemic, women must be given protection and knowledge in facing the COVID-19 pandemic.Based on the research results, it is concluded that to prevent and deal with the impacts that occur on reproductive health in women of childbearing age, health workers and community leaders can further increase the provision of education to the public, especially women, about healthy lifestyles during the COVID-19 pandemic.